Penatalaksanaan Fisioterapi Pada Kasus Calcaneus Spur Dekstra Di RSUD Dr. Soetomo Surabaya - Mufti Septiani, Riza; , Yulisna Mutia Sari, M.sc, (GRS) (2015)
Background: Calcaneus spur preceded by repeated injury to the plantar aponeurosis adhesions where the calcaneus. Calcaneus spur are bony protrusion on the bottom surface of the calcaneus due to calcium deposits that cause pain when walking. Objective: To determine whether ultrasound and exercise therapy can reduce tenderness and movement on the right heel, Gastroke muscle spasm, and increase the strength of the flexor muscles of the dorsal and plantar flexors. Results: After doing therapy at 6 times the results obtained, painful silence while the T6 T1 = 2 = 1, tenderness T1 = 6 while the T6 = 3, painful motion T1 = 3 while the T6 = 1. Results dorsal flexor muscle strength T1 = 4 - while the T6 = 4+, plantar flexors T1 = 4- whereas T6 = 5, Inversor T1 = 4- whereas T6 = 4+, eversor T1 = 4- whereas T6 = 5. Results M. Gastroke spasm on T1-T3 = spasm still there, T4-T6 = spasm is reduced. Results of functional ability to stand from a sitting position, pain and T6 T1 = 3 = 2, difficulty T1 = 2 and T6 = 1, the dependence T1 = 1 and T6 = 1, weeks to walk 15 meters, pain and T6 T1 = 2 = 1, difficulty T1 = 2 and T6 = 1, the dependence T1 = 1 and T2 = 1, and go up the stairs three traps, pain and T6 T1 = 2 = 1, the difficulty of T1 = 1 and T6 = 1, the dependence T1 = 1 and T6 = 1. Conclusion: Ultrasound and Therapeutic Exercise can reduce the pain still, motion and pressure, decrease muscle spasm gastroke, increase muscle strength dorsi flexion and plantar flexion and improved functional ability.